The influence of organizational culture on the implementation of learning organization among non-academic staff in UiTM, Kedah / Farah Wahidahani Hamsah and Hafizilina Abdul Ghani - Hamsah, Farah Wahidahani; Abdul Ghani, Hafizilina (2010)
This research is purposed to identify the currently dominating organizational culture, to measure the implementation of learning organization as well as to analyze the correlation between the organizational culture and the learning organization among Non-academic Staff in UiTM, Kedah via questionnaires. This paper consists of two parts. First, the organizational culture that applied in Majlis Perbandaran Sungai Petani Kedah (MPSPK) has been examined through the Organizational Culture Assessment Instrument (OCAI) by Cameron & Quinn (1999). Second, the implementation of learning organization among Non-academic Staff in UiTM, Kedah has been investigated with the Dimension of the Learning Organization Questionnaire (DLOQ) by Watkins & Marsick (1996). The recommendations will be emerge by evaluated the results that were obtained from both instruments.